2014
DOI: 10.1007/s00701-014-1994-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of sympathectomy on the regulation of basilar artery volume changes in stenoocclusive carotid artery modeling after bilateral common carotid artery ligation: an animal model

Abstract: Sympathectomy causes basilar artery enlargment, which is beneficial for maintaining cerebral blood flow; however, it also causes wall thinning, elongation, convolution, and aneurysm formation, which may be hazardous in stenoocclusive carotid artery disease. Sympathectomy can prevent new vessel formation and hyperthyrophic changes at the posterior circulation. Neovascularisation is not detected adequately in sympathectomised animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…High neuron density in stellate ganglia may protect against steno-occlusive carotid artery disease by preventing BA dilatation and aneurysm formation in the posterior circulatory arteries (7). Sympathetic hyperactivity of superior cervical ganglia prevents the severity of dilatation of basilar arteries after bilateral common carotid artery ligation (BCCAL) (8). BCCAL may lead to important beneficial and hazardous histomorphological changes at the posterior communicating artery.…”
Section: Discussionmentioning
confidence: 99%
“…High neuron density in stellate ganglia may protect against steno-occlusive carotid artery disease by preventing BA dilatation and aneurysm formation in the posterior circulatory arteries (7). Sympathetic hyperactivity of superior cervical ganglia prevents the severity of dilatation of basilar arteries after bilateral common carotid artery ligation (BCCAL) (8). BCCAL may lead to important beneficial and hazardous histomorphological changes at the posterior communicating artery.…”
Section: Discussionmentioning
confidence: 99%
“…(46) In one of our recent studies we reported widespread vascular remodeling including extensive arterial expansion, aneurysmal bulging, and severe vascular tortuosity throughout the rabbit CoW at 5 days and 6 months after bilateral CCA ligation. (5) In a follow-up study, we further investigated the effect of additional aneurysm risk factors (hypertension and estrogen deficiency) on the development of these vascular changes in the rabbit and demonstrated more widespread aneurysmal changes and more sever tortuosity at 6 months compared to CCA ligation alone.…”
Section: Discussionmentioning
confidence: 99%
“…(5) In a follow-up study, we further investigated the effect of additional aneurysm risk factors (hypertension and estrogen deficiency) on the development of these vascular changes in the rabbit and demonstrated more widespread aneurysmal changes and more sever tortuosity at 6 months compared to CCA ligation alone. (6) Furthermore, Eseoglu et al(4) explored the role of the sympathetic nervous system on BA remodeling by using the rabbit bilateral CCA ligation model and observed flattening of the inner elastic membrane and dilation of the BA at 2 months. Noting the similarities between these aneurysmal changes and BT aneurysm formation (IEL damage and bulging), we suspect that CCA ligation also produces aneurysm-initiating hemodynamics (high WSS and positive WSSG) at many locations in the rabbit CoW in addition to BT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications that may develop during the operation include esophagus perforations, vessel-nerve injuries, cerebral ischemias secondary to long-lasting excessive retraction of the carotid artery, lesion of the sympathetic plexus in the carotid artery wall, vocal cord paralysis secondary to recurrent laryngeal nerve traumas, and injuries to the medulla spinalis, dura mater, and the roots. [ 11 12 13 14 15 16 ] Postoperative complications are dislocations of the cage, neighboring segment syndrome, and infections. These types of complications are not observed in operations performed through posterior cervical laminoforaminotomy.…”
Section: Discussionmentioning
confidence: 99%